Pengaruh Locus of Control Internal dan Literasi Ekonomi dan Keuangan terhadap Perilaku Konsumtif Mahasiswa - Hutasoit, Christanti Oktasya; Siahaan, Mian; Pardede, Sanggam (Indo-MathEdu Intellectuals Journal, 2024)
The problem in this study is to determine the effect of internal locus of control and economic and financial literacy on the consumer behavior of 2020 and 2021 students of the economics education study program. This research was conducted at the Teacher Training and Education Department of HKBP Nommensen University, Medan with a population of 64 2020 and 2021 students of the economics education study program, the sampling technique in this study used the total sampling method. The data collection techniques used were observation, documentation, and questionnaires. The prerequisite tests used were the normality test, homogeneity test, multicollinearity test, and linearity test, the data analysis techniques used were descriptive statistical tests, t-tests (partial hypothesis testing), F-tests (simultaneous hypothesis testing), and coefficient of determination (R2). The results of the study showed that internal locus of control (X1) had a partial influence on consumer behavior (Y) with a t-count value <t-table (3.212> 1.998). And the variable of economic and financial literacy (X2) has an influence value of t-count < t-table (3.750 >1.998). So, in this research Internal Locus of Control influences economic and financial literacy and student consumption behavior